Modifications of Surface Properties of Biochar by Different Treatment Methods - Rafeah, Wahi; Muhammad Imran, Shaukat; Zainab, Ngaini; Nur Fakhirah Qurratu’ain, Zuhaidi (Springer, Singapore, 2024)
Biochar is a value-added product of biomass which is thermochemically synthesized. Application of biochar covers different processes/activities including environmental remediation, water purification, catalysis, tissue engineering, additive in organic waste compost, electrode material and modifier, and so on. Biochar is modified with respect to the target application. Different types of physical and chemical modifications have been reported. For application as adsorbent, pristine biochar exhibits lower surface area in comparison with the commercial activated carbon and this shortcoming necessitates appropriate treatment to make the biochar an effective adsorbent with larger surface area and improved surface properties. Modification process can be physical, or chemical, or a combination of both the treatment. Physical treatment entails enhancing the porosity, surface area, pore volume, and other physical features of biochar by activating its surface morphologies and properties. Chemical modification involves the use of solvents, acids/bases, or other substances to change and improve the functionality, pore structure, and surface area of biochar and can entail both one-step and two-step modification procedures. The current chapter highlights recent advances in physical and chemical treatment of the biochar, outlining major effects on the surface properties of the biochar.